Multi-stimulus linear negative expansion of a breathing M(O2CR)4-node MOF. (12th November 2020) - Watkins, Daniel; Roseveare, Thomas M.; Warren, Mark R.; Thompson, Stephen P.; Fletcher, Ashleigh J.; Brammer, Lee
Abstract : Quartz-type MOF (Me2 NH2 )2 [Cd(NO2 BDC)2 ] (SHF-81 ) exhibits anisotropic breathing behaviour as single crystals in response to multiple stimuli. Abstract : The metal–organic framework (Me2 NH2 )2 [Cd(NO2 BDC)2 ] (SHF-81 ) comprises flattened tetrahedral Cd(O2 CR)4 2− nodes, in which Cd(ii ) centres are linked via NO2 BDC 2− ligands (2-nitrobenzene-1, 4-dicarboxylate) to give a doubly interpenetrated anionic network, with charge balanced by two Me2 NH2 + cations per Cd centre resident in the pores. The study establishes that this is a twinned α-quartz-type structure (trigonal, space group P 3 x 21, x = 1 or 2), although very close to the higher symmetry β-quartz arrangement (hexagonal, P 6 x 22, x = 2 or 4) in its as-synthesised solvated form [Cd(NO2 BDC)2 ]·2DMF·0.5H2 O (SHF-81-DMF ). The activated MOF exhibits very little N2 uptake at 77 K, but shows significant CO2 uptake at 273–298 K with an isosteric enthalpy of adsorption (Δ H ads ) at zero coverage of −27.4 kJ mol −1 determined for the MOF directly activated from SHF-81-DMF . A series of in situ diffraction experiments, both single-crystal X-ray diffraction (SCXRD) and powder X-ray diffraction (PXRD), reveal that the MOF is flexible and exhibits breathing behaviour with observed changes as large as 12% in the a - and b -axes (|Δ a |, |Δ b | < 1.8 Å) and 5.5% in the c -axis (|Δ c | < 0.7 Å). Both the solvated SHF-81-DMF and activated/desolvated SHF-81 forms of the MOF exhibit linear negative thermal expansion (NTE), in which pores that run parallel to the c -axis expand in diameter ( a - and b -axis) while contracting in length ( c -axis) upon increasing temperature. Adsorption of CO2 gas at 298 K also results in linear negative expansion (Δ a, Δ b > 0; Δ c < 0; Δ V > 0). The largest change in dimensions is observed during activation/desolvation from SHF-81-DMF to SHF-81 (Δ a, Δ b < 0; Δ c > 0; Δ V < 0). Collectively the nine in situ diffraction experiments conducted suggest the breathing behaviour is continuous, although individual desolvation and adsorption experiments do not rule out the possibility of a gating or step at intermediate geometries that is coupled with continuous dynamic behaviour towards the extremities of the breathing amplitude.